Measurement of the triple gluon vertex from double quark tagged 4-jet events - Abreu, P; Adam, W; Adye, T; Adzic, P; Alekseev, G; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; Antilogus, P; et al. (1997)
The 4-jet events collected by the DELPHI experiment at LEP1 in 1992, 1993 and 1994 are analysed to determine the contribution of the triple-gluon vertex. Two of the four jets are tagged as jets from b-or c-quarks using lifetime and lepton transverse momentum information. The 4-jet contributions from double-gluon brems Strahlung, the triple-gluon vertex, and secondary quark-antiquark pair production then yield significantly different two-dimensional distributions in the generalized Nachtmann Reiter angle versus the opening angle of the two secondary jets. These distributions are used to fit CA/CF, the ratio of the coupling strength of the triple-gluon vertex to that of gluon bremsstrahlung, and NC/NA, the ratio of the number of quark colours to the number of gluons, giving CA/CF = 2.51 ± 0.28 and NC/NA = 0.38 ∓ 0.10 in agreement with the values expected from QCD: CA/CF= 9/4 = 2.25 and NC/NA = 3/8 = 0.375. © 1997 Published by Elsevier Science B.V.